Porcine uterus cryopreservation: an analysis of contractile function using different uterotonics - Schölch, Daniel; Schölch, Sebastian (Cryobiology, 2012)
Cryopreservation of whole organs has become increasingly successful in recent years, and establishing reliable methods for confirming the success of specific cryopreservation procedures has therefore become extremely important. On the assumption that methods such as histological evaluation do not provide definitive evidence of long-term cryopreservation and that clear signs of conserved function in an organ are good evidence of its viability, contractile function was analysed in porcine uteri (n=60), either after long-term (group A) or short-term (group B) cryopreservation and post-thaw treatment with three different uterotonics. A slow freezing protocol was used to preserve the organs. Fifteen fresh uteri were analysed similarly for contractile function, which was evaluated by measuring intrauterine pressure after administration of oxytocin, prostaglandin E1 (PGE1), and carbachol. After cryopreservation, all but three uteri (95%) showed rhythmic contractions similar to those in fresh uteri except for differences in the heights of contraction peaks, with lower contractions in PGE1 subgroup B (P<0.05). With the exception of three nonresponsive uteri in group A, there were no differences in contractility between uteri after long-term cryopreservation and fresh uteri. The results of this study thus contribute to the debate on whether slow freezing or vitrification techniques are best for whole-organ cryopreservation. In summary, (1) preservation of muscular function in porcine uteri is feasible with a slow freezing protocol; (2) measurement of contractile function following administration of uterotonics is a useful method of confirming functionality; and (3) long-term cryopreservation does not significantly impair post-thaw contractibility in comparison with fresh uteri.